2008
DOI: 10.1007/s11252-008-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of aesthetic, biological, and economic effectiveness of different lawn management programs

Abstract: We evaluated aesthetic (lawn quality), biological (weeds and insect pests), and economic (management costs) effectiveness of a commercial (managed by a professional company), consumer (managed using consumer lawn care products following labeled instructions), integrated pest management (IPM) (pesticide applications based on monitoring and thresholds), organic (monitoring and need-based organic and natural product applications), and an untreated lawn care program. Percent weed cover was the lowest in the commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…This is consistent with findings of Alumai et al (2008) who evaluated aesthetic, biological, and economic effectiveness of several lawn management programs in an experimental setup on the Ohio Agricultural Research and Development Center (OARDC) campus, including an IPM and a commercial program (managed by a different professional lawn care operator). That study found that the commercial lawn management program had higher lawn quality and cost than the IPM program.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with findings of Alumai et al (2008) who evaluated aesthetic, biological, and economic effectiveness of several lawn management programs in an experimental setup on the Ohio Agricultural Research and Development Center (OARDC) campus, including an IPM and a commercial program (managed by a different professional lawn care operator). That study found that the commercial lawn management program had higher lawn quality and cost than the IPM program.…”
Section: Discussionsupporting
confidence: 86%
“…One approach to reducing lawn chemical inputs, while still maintaining good lawn quality, is to implement integrated pest management (IPM) in lawn care (Alumai et al 2008). IPM promotes the use of multiple tactics, such as, cultural practices, biological control agents, and the use of chemical pesticides only when justified through pest monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In surveys from Ohio, North Carolina and Oregon, approximately 16-43% of households use professional landscaping services (Robbins et al 2001;Osmond and Hardy 2004;Nielson and Smith 2005), while 70% of US households cared for at least one aspect of their own yard (NGA 2007). Professionally maintained yards often rank higher in aesthetic lawn quality, as measured through grass color (greenness) and a lack of weeds (monoculture), than do-it-yourself approaches (Cheng et al 2008;Alumai et al 2009). Lush, green monoculture lawns result from frequent irrigation, herbicide application, and the use of time-release fertilizers (Nielson and Smith 2005).…”
Section: Management Decisionsmentioning
confidence: 99%
“…However, mainly for aesthetic reasons, these green spaces are sometimes intensively managed (frequently mowed and highly treated), leading to additional management costs (Caceres, Bigelow, & Richmond, 2010), serious threats to human health (Alumai, Salminen, Richmond, Cardina, & Grewal, 2009;Pimentel, 2005;Steingraber, 2002) and the environment (Byrne, 2005;Byrne & Bruns, 2004;Colborn & Short, 1999). Despite their potentially high ecological, educational and research benefits, urban lawns are still poorly studied ecosystems.…”
Section: Introductionmentioning
confidence: 99%